Influence of the air inlet configuration on the performances of a paraglider open airfoil. (2016) - Belloc, Hervé; Chapin, Vincent; Manara, Francesco; Sgarbossa, Francesco; Forsting, Alexander Meyer
A finite volume flow solver was used to solve the Reynolds averaged Navier-Stokes equations for the 2D flow field on a paraglider open airfoil. The canopy was assumed to be smooth, rigid and impermeable. The parametric study performed concerns the position and the width of the air inlet at the leading edge. The range of values used covers the air inlet geometries from classical ram-air parafoil to sport paraglider airfoil, including transition towards the full closed baseline airfoil. Results are focused both on lift and drag coefficients for performance analysis and on the internal pressure coefficient, which can be critical for a real flexible wing regarding the risk of collapse. Depending on the appearance of a separation bubble over the upper edge, two well separated behaviours can be observed. The first behaviour is more typical of ram-air parachutes and the second one corresponds to the design of performance paragliders. For paraglider configurations, it is shown that the aerodynamic coefficients of the open airfoil can be easily deduced from the pressure coefficients of the baseline airfoil without solving the internal flow.